Mixed germ cell tumor of the endometrium: a case report and literature review - Zhang Heping; Liu Fangyun; Wei Jianguo; Xue Debin; Xie Zhengxin; Xu Chunwei (Open Medicine, 2020)
Germ cell tumors (GCTs) localized extragonadally are rare, with only 14 reported cases of a yolk sac tumor in the endometrium. Here we report a case of mixed endometrium GCTs in a 65-year-old postmenopausal woman with abnormal vaginal bleeding. An ultrasound examination showed an oval-shaped mass in the patient’s uterine cavity. Biochemical examination revealed elevated serum α-fetoprotein (AFP) at 359 ng/mL, whereas the tumor markers CA-125, CA-199, and CEA were all within normal range. Total hysterectomy and bilateral salpingo-oophorectomy were performed;. a histological examination revealed that the malignant components contained a yolk sac tumor, embryonal carcinoma, and focal immature teratoma. Immunohistochemical staining showed that AFPs were diffusively distributed in both the yolk sac tumor and embryonal carcinoma. The stem cell marker OCT3/4 was positive in the embryonal carcinoma component and that the pan-cytokeratin AE1/AE3 staining was positive in glandular areas. GFAPs (Glial Fibrillary Acidic Proteins) were positive in neuroectodermal tubules; the Ki-67 protein was positive in 90% of the tumor cells, whereas CD117 and placental alkaline phosphatase (PLAP) were negative. The cumulative evidence indicated mixed GCTs of endometrium as the final histopathological diagnosis. The patient received three courses of adjunct chemotherapy that provided good therapeutic efficacy as evidenced by the decreased serum AFP level. Our report on this rare case of mixed GCTs of the endometrium, supported by associated histological patterns and immunophenotypes and successful adjunct chemotherapy after surgery, could provide insight on future treatment of this rare but lethal disease.